Formation of median nerve by three roots: A case report - Satyanarayana, N; Reddy, CK; Sunitha, P; Jayasri, N; Nitin, V; Praveen, G; Guha, R; Datta, AK; Shaik, MM (Journal of College of Medical Sciences-Nepal, 2010)
During routine dissection of an adult male cadaver in the Department of Anatomy, College of Medical Sciences, Bharatpur, Nepal, the right median nerve was found to be formed by three roots. The finding was noted after thorough and meticulous dissection of the upper limbs of both sides (axilla, arm, forearm and palm). Out of the three roots forming the anomalous median nerve, two were from lateral cord and one from medial cord of brachial plexus. However, the distribution of the anomalous median nerve was normal in arm, forearm and palm. The arterial pattern in the arm (axillary and brachial arteries) was also normal. Key words: Cadaver; median nerve; brachial plexus DOI: 10.3126/jcmsn.v6i1.3602 Journal of College of Medical Sciences-Nepal, 2010, Vol. 6, No. 1, 47-50